Considerações clínicas em implantes imediatos - Martins, Cinthia Azevedo [UNESP] (2010)
The biological principles of osseointegration caused the rehabilitation treatment with osseointegrated implant become a safe, well alternative accepted by the dental community for the high success rate, allowing the preparation of functional and aesthetic prostheses in edentulous and partial patients. We passed the initial phase of functional vision for an aesthetic approach, too, depending on the demands of the patient and the quest for excellence by professionals. Over these last years, implant treatment has undergone many changes in surgical and prosthetic protocols. The less invasive surgical techniques and the development of restorative materials, especially ceramics allow the prosthetic rehabilitation of high functional quality and aesthetics. The installation of implants in sockets immediately after extraction of teeth involved by fracture, periodontal disease, endodontic lesions, is part of the arsenal of techniques for rehabilitating a number of advantages that we get to the outcome of multidisciplinary treatment. For this, we must consider several criteria in its planning as a fundamental unit, adjacent teeth, multiple losses, system, form and number of implants, type of retention of the prosthesis components, the patient expectation of the outcome perspective, gingival biotype, standard of ridge resorption, the smile line, etc. occlusal analysis. With the three-dimensional placement of the implant can immediately join the biological processes of repair of the socket, implant osseointegration, speeding treatment time. Much has been made by companies in the surface treatment of endosseous implants to be osseointegration shortened and restorative procedures started earlier, bringing benefits to the patient and professional. Among the main advantages we can emphasize the preservation of the structures adjacent to the teeth replaced, minor resorption of bone tissue involved... (Complete abstract click electronic access below)